Burnout syndrome in the work environment of workers in a company in the city of Riobamba, Ecuador - Karina Alexandra Álvarez Basantes; Doris Nataly Gallegos Santillan; Veronica Adriana Carrasco Salazar; Cristofher César Balcázar Vivanco; Jeovanna Viviana Tacuri Castro (Revista Habanera de Ciencias Médicas)
Introduction: Burnout syndrome is defined as the mental, emotional and physical exhaustion caused by work, characterized by 3 fundamental dimensions: physical fatigue, depersonalization, and personal fulfilment. In workers of the Unión Cementera Nacional, Ecuador, traits of the syndrome have been identified.